2013
DOI: 10.1002/pds.3410
|View full text |Cite
|
Sign up to set email alerts
|

Safe lists for medications in pregnancy: inadequate evidence base and inconsistent guidance from Web‐based information, 2011

Abstract: Women who see a medication on one of these 'safe' lists would be led to believe that there is no increased risk of birth defects resulting from exposure. Thus, women are being reassured that fetal exposure to these medications is safe even though a sufficient evidence base to determine the relative safety or risk does not exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 9 publications
1
42
0
3
Order By: Relevance
“…However, in each case, we do not know which source came first, in which order the information was sought, or the actual content of the information received. There is evidence of a lack of consistency between information on drug safety during pregnancy based on different information sources [23-25]. For example, according to the study by Frost Widnes and Schjøtt [24], the Norwegian Compendium on Product Monographs gives advice which is more restrictive than that given by drug information centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in each case, we do not know which source came first, in which order the information was sought, or the actual content of the information received. There is evidence of a lack of consistency between information on drug safety during pregnancy based on different information sources [23-25]. For example, according to the study by Frost Widnes and Schjøtt [24], the Norwegian Compendium on Product Monographs gives advice which is more restrictive than that given by drug information centers.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate dissemination of appropriate advice describing which drugs may be continued can lead to women unnecessarily forgoing potentially helpful medications and thus suffering throughout pregnancy, with the increased risk of further complications to both mother and child due to the effects of active disease 26. Furthermore, patients are increasingly seeking additional information on the internet,27 while a recent analysis of information regarding medication safety on active internet sites has noted an inadequate evidence base for the advice often provided and inconsistent guidance 28. It is clear that communication of reliable and consistent information is required to enable the correct treatment of these women before and during pregnancy, and while breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are worrisome as neither the Internet or health food store sources have been found to be solid sources of reliable information. A recent study examined websites providing lists of prescription medications reported to be safe during pregnancy; inconsistent and inaccurate information about those drugs was found (Peters et al, 2013). With even less empirical data related to CAM therapies it is likely that Internet information is largely inaccurate as well.…”
Section: Discussionmentioning
confidence: 99%